Active directory cookbook - Allen, Robbie (O'Reilly, 2003)
Those of you who run networks on Windows 2000 know the benefits of using Active Directory for managing user information and permissions. You also know what a bear it can be. The newer version included with Windows Server 2003 has over 100 new and updated features to simplify deployment, but once it's in place many system administrators still find Active Directory challenging. If you're among those looking for practical hands-on support, help is here with our new Active Directory Cookbook for Windows Server 2003 and Windows 2000 , a unique problem-solving guide that offers quick answers for both versions of the directory. The book contains hundreds of step-by-step solutions for both common and uncommon problems that you might encounter with Active Directory on a daily basis--including recipes to deal with the Lightweight Directory Access Protocol (LDAP), multi-master replication, Domain Name System (DNS), Group Policy, the Active Directory Schema, and many other features. Author Robbie Allen, a Senior Systems Architect at Cisco Systems and co-author of our Active Directory tutorial, based this collection of troubleshooting recipes on his own experience, along with input from Windows administrators throughout the industry. Each recipe includes a discussion to explain how and why the solution works, so you can adapt the problem-solving techniques to similar situations. If your company is considering an upgrade from Windows NT or 2000 to Windows Server 2003, the Active Directory Cookbook for Windows Server 2003 and Windows 2000 will help reduce the time and trouble it takes to configure and deploy Active Directory for your network. This Cookbook is also a perfect companion to Active Directory, the tutorial that experts hail as the best source for understanding Microsoft's network directory service. While Active Directory provides the big picture, Active Directory Cookbook for Windows Server 2003 and Windows 2000 gives you the quick solutions you need to cope with day-to-day dilemmas. Together, these books supply the knowledge and tools so you can get the most out of Active Directory to manage users, groups, computers, domains, organizational units, and security policies on your network.